Maharashtra State BoardHSC Arts 12th Board Exam
Advertisement Remove all ads

Using the rule of negation write the negation of the following with justification. (p ∨ ∼ q) → (p ∧ ∼ q) - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Using the rule of negation write the negation of the following with justification.

(p ∨ ∼ q) → (p ∧ ∼ q)

Advertisement Remove all ads

Solution

The negation of (p ∨ ∼ q) → (p ∧ ∼ q) is
∼ [(p ∨ ∼ q) → (p ∧ ∼ q)] ≡ (p ∨ ∼ q) ∧ ∼ (p ∧ ∼ q) ..........(Negation of implication)
≡ (p ∨ ∼ q) ∧ [∼ p ∨ ∼ (∼ q)] .............(Negation of conjunction)
≡ (p ∨ ∼ q) ∧ (∼ p ∨ q) .........(Negation of negation)

Concept: Negations of Compound Statements
  Is there an error in this question or solution?

APPEARS IN

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×